2020
DOI: 10.15845/voices.v20i2.2869
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Singing Engagement on Food Intake of Individuals with Alzheimer’s Disease and Related Dementias: A Multi-site, Repeated Measures Study

Abstract: Malnutrition among older adults with Alzheimer’s disease and related dementias (ADRD) is a serious and long-recognized health concern. Identifying nonpharmacological means for enhancing the volume of nutrition intake is an urgent need. Researchers have explored the use of music and music therapy as nonpharmacological avenues in this regard, but most music-based studies related to food intake focus on receptive interventions wherein participants are exposed to recorded music during meal times. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…An RCT (n = 15) found no significant change, and attributed this to small participant numbers and inconsistencies in study adherence (McHugh et al, 2012). A pre-post study (n = 28) similarly noted no significant change, however, they also observed that food intake was greater during the baseline measurements than following intervention for residents at two out of three facilities (Hiller, 2020). The authors speculated that this could potentially be related to an increase in serotonin (due to singing), which has been known to suppress appetite, although owing to small sample sizes, this warrants further investigation.…”
Section: Activities Of Daily Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…An RCT (n = 15) found no significant change, and attributed this to small participant numbers and inconsistencies in study adherence (McHugh et al, 2012). A pre-post study (n = 28) similarly noted no significant change, however, they also observed that food intake was greater during the baseline measurements than following intervention for residents at two out of three facilities (Hiller, 2020). The authors speculated that this could potentially be related to an increase in serotonin (due to singing), which has been known to suppress appetite, although owing to small sample sizes, this warrants further investigation.…”
Section: Activities Of Daily Livingmentioning
confidence: 99%
“…Five studies measured the impact of singing on Activities of Daily Living (ADL) for people living with dementia (Table 7) (Camic et al, 2011;McHugh et al, 2012;Satoh et al, 2015;Lyu et al, 2018;Hiller, 2020). Three studies used standardised measures to examine the effect on overall ADL.…”
Section: Activities Of Daily Livingmentioning
confidence: 99%
“…Malnutrition, in their case, is affected, not only by age-related changes, but also by the disease itself. Studies show that changes in the central nervous system (CNS) in people with Alzheimer’s disease also apply to centers responsible for controlling appetite and regulating food consumption [ 35 , 36 ].…”
Section: Nutrition In the Prevention And Alzheimer’s Diseasementioning
confidence: 99%